Validating the accuracy of Omron J760 electronic blood pressure monitor in the general population according to AAMI/ESH/ISO (ISO 81060-2:2018) + AMD1:2020 - Bihua Chen; Guorong Chen; Hong Jiang; Ya Sun; Jie Chen; Dan Wang; Mingzhi Chen; Jia Shi; Yan Peng; Yimin Cheng; Cheng Yang; Yuanyuan Ding; et al. (Blood Pressure)
Purpose The accuracy of the Omron J760 electronic blood pressure (BP) monitor for upper arm BP measurement in the adult general population was validated following the AAMI/ESH/ISO (ISO 81060-2:2018) + Amd1:2020 protocol. We expect that this device can be used for home blood pressure monitoring, with its measurements serving as a clinical reference.Methods Subjects meeting the age, gender, BP, and cuff distribution criteria as specified by the AAMI/ESH/ISO (ISO 81060-2:2018) + Amd1:2020 were recruited. BP measurements were conducted using the same-arm sequential method. The test device cuff was suitable for arm circumferences ranging from 22.0 cm to 42.0 cm.Results Eighty-nine participants were initially recruited, 85 were evaluated after excluding 4 participants. The mean age of the participants was 48.5 ± 15.17 years. For validation criterion 1, the mean ± standard deviation (SD) of the differences between the test device and the reference BP measurements were 0.2 ± 5.74 mmHg for systolic BP and −0.9 ± 4.69 mmHg for diastolic BP. These results met the AAMI/ESH/ISO (ISO 81060-2:2018)+Amd1:2020 standard, which requires differences of ≤5 ± ≤8 mmHg. For validation criterion 2, the mean differences between the test device and the reference device were 0.2 ± 5.10 mmHg for systolic BP and −0.9 ± 4.30 mmHg for diastolic BP. This criterion was satisfied with criterion 2 of ≤6.95 mmHg for systolic BP and ≤6.88 mmHg for diastolic BP.Conclusion The Omron J760 electronic BP monitor meets the requirements of the AAMI/ESH/ISO (ISO 81060-2:2018)+Amd 1:2020 validation standard.